24 X 7: The Sunderland Experience - Archer, Julie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The University of Sunderland is committed to widening participation. This means we attract a wide range of students from the non-traditional higher education sector, and an increasing population of international students. The need to support and develop these students’ study skills is important and the libraries are seen as central to the strategy in providing both quality learning environments and resources. We are aware of factors such as almost 90% of our students also have part time jobs; increasingly our students can be based in a partner college or are distance learners. Our commitment to learners should be proactive, in providing a quality-learning environment when they need it regardless of their personal life styles and commitments. The need to provide flexible access is vital and was an important planning factor when looking at our service provision and developing the buildings. Libraries also have an important role in supporting student recruitment and retention. To be customer focused we need to recognise students’ pastoral needs where they affect their learning needs, and in the case of international students this may include making provision for real time contact with their families. Meanwhile the University is developing a two-campus profile, having been for many years spread throughout the city. The libraries are seen as focus points for study places, print and electronic resources.